2020
DOI: 10.1155/2020/5481653
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Compound Herbal Medicine Tong-Xie-Yao-Fang for Acute Radiation Enteritis and Its Potential Mechanisms: Evidence from Transcriptome Analysis

Abstract: Acute radiation enteritis (ARE) is a common complication with radiotherapy for pelvic and abdominal malignancy. This research is designed to investigate the efficacy of Tong-Xie-Yao-Fang (TXYF) on ARE and to explore the underlying mechanisms by microarray analysis. The ARE rat model was established by a single abdominal irradiation with a gamma-ray dose of 10 Gy. Next, the ARE rats were treated with distilled water, TXYF, and glutamine by gavage for 7 consecutive days according to the scheduled groups. For eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…RIII prevention and treatment research is mainly focused on natural antioxidants (such as vitamins and amino acids), known body protectors, newly synthesized compounds, and biotechnological methods. [7][8][9] A large number of studies have shown that Chinese medicines or extracts may alleviate radiation damage, [10][11][12][13][14] and also have protective effects on radiation enteritis, 15,16 including menthol and ginseng, which are attracting increasing attention due to their low toxicity and are used for radiation protection and treatment. 17,18 Therefore, Chinese medicine compounds may be effective in RIII protection and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…RIII prevention and treatment research is mainly focused on natural antioxidants (such as vitamins and amino acids), known body protectors, newly synthesized compounds, and biotechnological methods. [7][8][9] A large number of studies have shown that Chinese medicines or extracts may alleviate radiation damage, [10][11][12][13][14] and also have protective effects on radiation enteritis, 15,16 including menthol and ginseng, which are attracting increasing attention due to their low toxicity and are used for radiation protection and treatment. 17,18 Therefore, Chinese medicine compounds may be effective in RIII protection and therapy.…”
Section: Introductionmentioning
confidence: 99%